Septian Tri Saputra Pengaruh Kualitas Pelayanan, Kualitas Makanan dan variasi Menu Seimbang Terhadap Kepuasan Karyawan Pada Kantin Hotel Bintang 5 di Jakarta - Septian Tri Saputra; Meylani Tuti (Human Capital Development, 2022)
This study aims to analyze the effect of service quality, food quality, balanced menu variations on employee satisfaction. The population in this study are permanent employees of 5-star hotels in Jakarta. The sampling technique used is purposive sampling, namely respondents who have become permanent employees of 5-star hotels in Jakarta and obtained a total sample of 200 people. To test the proposed hypothesis, this study uses the PLS-SEM (Partial Least Squares- Structural Equation Modeling) approach. The PLS SEM analysis was carried out in two stages in 2 sessions. The initial stage is an analysis of reliability and validity, while the second session is the estimation and leveraging of the path coefficients and power of the structural model. This research uses the help of software SmartPLS 3.2.9. The results of this study indicate that there is a direct positive between Service Quality, Food Quality, and Menu Balance for employee satisfaction.